Normal vs. reverse fault – the example of curvature's usage on gravimetric data - KARCOL, Roland; PAŠTEKA, Roman (Contributions to Geophysics and Geodesy, 2020)
The gravitational effects caused by normal and reverse faults are very close to each other, both in amplitude and in the shape. We demonstrate the usage of the first curvature as a tool for the setting the slope orientation without the additional geological information. The curvature is calculated not only for the measured data, but for their upward continuation, too. This step helps to lower instability of the curvature computation and is important in the interpretation of the resultant curvature as well. We applied this method on the synthetic test and on the real regional gravimetric data as well. The results show the method could be useful step before the density modelling process and generally during qualitative interpretation in applied gravimetry.